1995
DOI: 10.1111/j.1399-3054.1995.tb02229.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of K+ and NO3 fluxes in roots of sunflower (Helianthus annuus) after changes in light intensity

Abstract: Shoot activity has been reported to affect rates of ion uptake by plant roots in other ways than merely through supply of assimilates. To elucidate the mechanisms by which a signal from the upper part of the plant controls the rate of K+ and NO3− uptake by roots, both uptake of K+ and NO3− and secretion into the xylem of young sunflower plants (Helianthus annuus L.) were measured after changes in light intensity. No close correlation was observed between the uptake of NO3− and that of K+; an increase in light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
1
16
1
Order By: Relevance
“…Isotopic data thus indicate that there was an slight imbalance between xylem nitrate input and nitrate reduction (consumption) in leaves, in favour of xylem input under high K and in favour of nitrate consumption under low K + waterlogging. This is consistent with previous data that showed that potassium was essential to facilitate nitrate circulation via a shoot‐root cycle where K + plays the role of a counter‐cation for nitrate (Casadesús, Tapia, & Lambers, ; Coskun, Britto, & Kronzucker, ; Wang & Wu, ). However, isotopes would not be consistent with an altered nitrate circulation under low K alone, but only under low K combined with waterlogging.…”
Section: Discussionsupporting
confidence: 93%
“…Isotopic data thus indicate that there was an slight imbalance between xylem nitrate input and nitrate reduction (consumption) in leaves, in favour of xylem input under high K and in favour of nitrate consumption under low K + waterlogging. This is consistent with previous data that showed that potassium was essential to facilitate nitrate circulation via a shoot‐root cycle where K + plays the role of a counter‐cation for nitrate (Casadesús, Tapia, & Lambers, ; Coskun, Britto, & Kronzucker, ; Wang & Wu, ). However, isotopes would not be consistent with an altered nitrate circulation under low K alone, but only under low K combined with waterlogging.…”
Section: Discussionsupporting
confidence: 93%
“…The Dijkshoorn–Ben Zioni model has proven useful in a large number of studies and provides one of the few mechanisms known to link shoot demand for nutrients with their uptake by the roots (Casadesús et al . ; Marschner et al . ).…”
Section: Transportmentioning
confidence: 99%
“…; Barneix & Breteler ; Förster & Jeschke ; Casadesús et al . ; Armengaud et al . ), which also depends on plant species, external nitrate supply, temperature and light intensity (Pate ; Smirnoff & Stewart ; Andrews ).…”
Section: Metabolismmentioning
confidence: 99%
“…However, the current techniques for measuring solutes are not advanced enough to continuously measure individual ion concentrations in single xylem vessels. Attempts in the last decades to estimate xylem solutes, among other things (Schurr, 1998), from guttation or bleeding fluids, from (pressurized) root exudates, from sap expressed from cut leaves by the pressure chamber technique or from ‘artificial guttation’ at leafy incisions by root pressurization of intact plants may be useful for various purposes, but they are ultimately inappropriate because of the dramatic implications of the manipulations on the highly coupled force‐flow relationships in higher plants (Casadesus et al ., 1995; Rygol et al ., 1993; Schurr and Schultze, 1995; White, 1997; Zimmermann et al ., 1992, 1993). Determination of xylem ion composition by cryo‐scanning electron microscopy (Canny, 1993, 1997) or by analysis of xylem sap extracted by a compression‐decompression cycle (Schill et al ., 1996; Zimmermann et al ., 2002b) yields more reliable values, but is still faced with the unpredictable collapse of ion gradients and re‐distribution upon plant organ excision.…”
Section: Introductionmentioning
confidence: 99%